The Relevance and Dynamics of Muamalat Transactions in the Context of Modern Economics: A Holistic Review - Aisyah Abdul Jabbar; Meguellati Achour; Edwards Geraldine; Ishmah Afiyah (Walidem Institute and Publishing, 2024)
The purpose of this study is to investigate the relevance and dynamics of muamalat transactions in the context of modern economics and present a holistic review of the topic. The research methods used are literature analysis and qualitative studies, which involve collecting data from various sources such as scientific literature, official documents, and related publications. The results show that muamalat transactions have a growing significance in the modern economy, not only as a financial instrument but also as a business model that promotes ethical values and justice. The dynamics of muamalat transactions are reflected in adjustments to technological developments and global market needs while maintaining the underlying sharia principles. This holistic review provides a deeper understanding of the role of muamalat transactions in creating an inclusive and sustainable economic ecosystem in the context of the modern economy.